Emergence of Salmonella enterica serovar Infantis infection in humans, Peru - García, Coralith (2019)
Introduction. Multidrug-resistant Salmonella Infantis have been isolated in Ecuador, Peru and Bolivia in the recent past years. Objectives. To evaluate the emergence and burden of Salmonella Infantis infection in a public hospital of Lima, Peru. Methods. We prospectively followed consecutive cases of salmonellosis at Cayetano Heredia hospital (October 2015-May 2017). Detection of invA gene by PCR and determination of serovars by a multiplex PCR were performed. Antimicrobial susceptibility was assessed by disk diffusion method. Detection of extended-spectrum β-lactamase phenotype was done by double disc method. Results. Seventy isolates from 50 patients were confirmed as Salmonella. Only one isolate per patient was further analyzed. The most frequent serovar detected was Infantis (n = 18; 36%), followed by Typhimurium and Enteritidis (n = 13, 26%, each). In thirty cases Salmonella was isolated only from stool, 14 were in children <= 2 years old (46.7%), and Infantis was detected in 17 cases (56.7%). Salmonella was detected in other source than stool in 20 cases, most of patients had different forms of immune suppression such as AIDS, chemotherapy, diabetes mellitus and kidney transplant. Most of these invasive cases were caused by Typhimurium (n = 9) and Enteritidis (n = 8); only one case was caused by Salmonella Infantis in a 1 year-old child. All Salmonella Infantis isolates (n = 18) produced ESBLs, and were only fully susceptible to carbapenems. Non-Infantis Salmonella isolates (n = 32) were susceptible to meropenem (100%), ceftriaxone (96.9%), trimethoprim-sulphametoxazole (87.5%), ampicillin (84.4%), chloramphenicol (78.1%), nalidixic acid (59.4%), and ciprofloxacin (37.5%). Conclusion. Multidrug-resistant Salmonella Infantis was the most frequent serovar displacing Enteritidis and Typhimurium. Most of cases were mainly presented as diarrheal illnesses among children. Compared to Infantis, other serovars showed higher rates of susceptibility to ‘old’ antimicrobials. Of note, the antibiotic with lowest rate of susceptibility was ciprofloxacin.